Obesity and Fatty Acids Promote Mitochondrial Translocation of STAT3 Through ROS-Dependent Mechanisms - Conway, Rachel; Rockhold, Jack Donato; SantaCruz-Calvo, Sara; Zukowski, Emelia; Pugh, Gabriella H.; Hasturk, Hatice; Kern, Philip A.; Nikolajczyk, Barbara S.; Bharath, Leena P. (Frontiers in Aging, 2022)
Obesity promotes the onset and progression of metabolic and inflammatory diseases such as type 2 diabetes. The chronic low-grade inflammation that occurs during obesity triggers multiple signaling mechanisms that negatively affect organismal health. One such mechanism is the persistent activation and mitochondrial translocation of STAT3, which is implicated in inflammatory pathologies and many types of cancers. STAT3 in the mitochondria (mitoSTAT3) alters electron transport chain activity, thereby influencing nutrient metabolism and immune response. PBMCs and CD4+ T cells from obese but normal glucose tolerant (NGT) middle-aged subjects had higher phosphorylation of STAT3 at residue serine 727 and more mitochondrial accumulation of STAT3 than cells from lean subjects. To evaluate if circulating lipid overabundance in obesity is responsible for mitoSTAT3, cells from lean subjects were challenged with physiologically relevant doses of the saturated and monounsaturated fatty acids, palmitate and oleate, respectively. Fatty acid treatment caused robust accumulation of mitoSTAT3 in all cell types, which was independent of palmitate-induced impairments in autophagy. Co-treatment of cells with fatty acid and trehalose prevented STAT3 phosphorylation and mitochondrial accumulation in an autophagy-independent but cellular peroxide-dependent mechanism. Pharmacological blockade of mitoSTAT3 either by a mitochondria-targeted STAT3 inhibitor or ROS scavenging prevented obesity and fatty acid-induced production of proinflammatory cytokines IL-17A and IL-6, thus establishing a mechanistic link between mitoSTAT3 and inflammatory cytokine production.